Sistem Resirkulasi Akuakultur Untuk Produksi Ikan Hias (Telaah Pustaka) - Ayi Yustiati; Agung Meidito Nugroho; Zahra Egidita Maharani; Mohammad Badai Putra Surahman; Yuli Andriani (Jurnal Perikanan Unram, 2024)
Ornamental fish have their own charm due to the beauty of their shapes and color patterns. Ornamental fish have good sales prospects and have high economic value, so many ornamental fish hobbyists and breeders are involved in them. Cultivating ornamental fish is certainly not free from obstacles, such as ponds or aquariums that have been contaminated with microbes which can cause fish to get sick or even cause death. One way to maintain fish health while increasing ornamental fish production is to monitor water quality. Efforts that can be made to overcome the above problems are to apply a recirculating aquaculture system. This study aims to provide information on the use of an effective aquaculture recirculation system to increase ornamental fish production while reducing ornamental fish mortality rates. The information that will be provided is a study from several journals regarding circuits for recirculation systems and optimizing the use of filter combinations in recirculation systems.